Isolation and Structure Determination of Banana Pseudostem Based Uro-Lignin (Journal of Bangladesh Academy of Sciences, 2010)
Lignin was isolated from wet Banana pseudostem with 2% NaOH solution by boiling. The isolated lignin was treated with urea and called uro-lignin. IR, Mass and NMR spectra of urolignin were taken to determine its molecular structure. DOI: 10.3329/jbas.v33i2.4106 Journal of Bangladesh Academy of Sciences, Vol. 33, No. 2, 227-229, 2009